ENDEMISM AND CONSERVATION STATUS OF TREE SPECIES OF FRESHWATER SWAMP FOREST, PERAK TENGAH, MALAYSIA - Liliwirianis Nawi; Mohd Nazip Suratman; Farida Zuraina Mohd Yusof; Abdul Latiff Mohamad (SEAMEO BIOTROP, 2024)
ARTICLE HIGHLIGHTS- Approximately 3,364 tree individuals with a diameter at breast height (dbh) of 10.0 cm and above were assessed in the Perak Tengah freshwater swamp forest. - The study has recognised 58 species identified are new to Perak.- 72 tree species are listed as endemic, and 194 species are listed in the Red List of Threatened Species by The International Union for Conservation of Nature (IUCN).- This study mphasize the need to preserve ecology and mitigate threats. ABSTRACTThe forests of Peninsular Malaysia have long been recognized as a significant home of endemic species. The purpose of this study was to assess the endemism and conservation status of tree species present in the Perak Tengah freshwater swamp forest. A total of 150 plots (20 m × 20 m) were established in the study area using a random sampling design. Approximately 3,364 tree individuals with diameter at breast height (dbh) of 10.0 cm and above were enumerated in all plots. In the study area, 58 species identified are new to Perak, 72 tree species are listed as endemic, and 194 species are listed in the Red List of Threatened Species by IUCN. Thus, it is crucial to preserve the ecology and lessen the impact of threats in the Perak Tengah freshwater swamp forest, which is home to numerous endemic and endangered species.